An Experimental Investigation on the Mechanical Properties of Gangue Concrete as a Roadside Support Body Material for Backfilling Gob-Side Entry Retaining. (17th January 2018) - Gong, Peng; Ma, Zhanguo; Ni, Xiaoyan; Zhang, Ray Ruichong
Abstract : Development of a safe and economical roadside support body (RSB) material is the key to successful backfilling gob-side entry retaining (GER). By means of laboratory tests, this paper studied the effects of the water-cement ratio, aggregate content, and age on the contractibility and resistance increasing speed, compressive strength, and postpeak carrying capacity of the concrete with gangues as an aggregate. It also discussed the rationality and adaptability of gangue concrete as a RSB material for backfilling GER. The experimental results show that the compressive strength of gangue concrete increases with age, and that the strength of gangue concrete demonstrates a nonlinear decreasing trend with the increase of the cementing material's water-cement ratio. The water-cement ratio in the range of 0.46–0.60 has the most significant regulation effect on the strength of gangue concrete. Mixing with a certain amount of coal gangue enhances the postpeak carrying capacity of concrete, preventing the sample from impact failure. The field experimental results report that as a RSB material, gangue concrete can meet the design and application requirements of GER with gangue backfilling mining. A RSB material featuring high safety, high waste utilization rate, fast construction speed, and low costs is provided.